Effects of the Residues of Cuscuta campestris and Mikania micrantha on Subsequent Plant Germination and Early Growth - Feng-lan LI; Ming-guang LI; Qi-jie ZAN; Qiang GUO; Wei-yin ZHANG; Zhi WU; Yong-jun WANG (Journal of Integrative Agriculture, 2012)
Cuscuta campestris, a dodder, can parasitize and suppress a scrambling herbaceous to semi-woody perennial vine, Mikania micrantha, one of the most destructive weeds in the world. To assess the effects of the mixed residue of C. campestris and M. micrantha on the subsequent plant community, we conducted a one-year experiment on the germination and seedling growth of subsequent plant community after the application of C. campestris. Seven treatments of varying proportions of C. campestris and M. micrantha residue on 21 subject trees and shrubs, which were commonly found in South China, resulted in a germination rate of 35.3% for all 8 715 seeds from 18 species, ranging from 5.7 to 81.9%; the remaining 3 species failed to germinate. ANOVA analysis showed that the residue did not affect the germination, growth, or mortality of the trees and shrubs. The germinated C. campestris seeds from the residue coiled the seedlings of most of the species, but less than 4% host death caused by C. campestris. In addition, the residue did not affect the germination of the herbaceous seedlings originating from the loam, and the similarity coefficients of the germinated seedlings between the treatments were very high. These results suggested that the residue had no negative impact on the germination and early seedling stages of the tree, shrub and grass species of the subsequent plant community. The use of C. campestris residue had a positive effect on the growth of M. micrantha, but it did not change the trend of M. micrantha being suppressed because re-parasitization occurred soon after the growth restarted. No negative effect was detected on the other species as a result of the parasitization of C. campestris or by the use of the mixed residue. This suggests that C. campestris is likely to be an effective and promising ecologically safe native herbaceous agent for controlling M. micrantha.